IDENTIFIKASI JENIS-IDENTIFIKASI JENIS-JENIS PAKAN ALAMI KUSKUS (PHALANGERIDAE) DI PULAU HARITI DISTRIK NAPAN WEINAMI KABUPATEN NABIRE PAKAN ALAMI KUSKUS (PHALANGERIDAE) DI PULAU HARITI DISTRIK NAPAN WEINAMI KABUPATEN NABIRE - Fernando Duwiri; Jan H. Nunaki; Freddy Pattiselanno (FMIPA Universitas Papua, 2010)
Possum as a marsupial animal belongs to the family Phalangeridae are spread quite widely on the island of New Guinea. There are many types of possums found in many small islands of Papua, among others, in the coastal areas of Napan Wenami, Nabire. Hariti Island is one of the group of islands in the District of Napan Weinami. This study aims to explore the kinds of natural food of possums on the island Hariti. The results of the study shows that there were 21 plant species eaten by possums, consisted of 17 families, where as the family Moraceae have the largest number of species. Plant parts that are consumed is fruit (43%), leaf (24%) and a combination of leaf and fruit (33%).